Multicentre, randomized, open-label study of on-demand treatment with two prophylaxis regimens of recombinant coagulation factor IX in haemophilia B subjects - Valentino, L. A.; Rusen, L.; Elezovic, I.; Smith, L. M.; Korth-Bradley, J. M.; Rendo, P. (Haemophilia : the official journal of the World Federation of Hemophilia, 2014)
Summary Few randomized studies have reported on the use of factor IX (FIX) for secondary prophylaxis in haemophilia B patients. This study aimed to evaluate the efficacy and safety of two secondary prophylaxis regimens of recombinant coagulation FIX, nonacog alfa, compared with on‐demand therapy. Male subjects aged 6–65 years with severe or moderately severe haemophilia B (FIX:C ≤ 2, n = 50) and ≥12 bleeding episodes (including ≥6 haemarthroses episodes) within 12 months of study participation were enrolled in this multicentre, randomized, open‐label, four‐period crossover trial. The primary measure was the annualized bleeding rate (ABR) of two prophylactic regimens vs. on‐demand therapy. In the intent‐to‐treat group, mean ABR values were 35.1, 2.6 and 4.6 for the first on‐demand period, the 50 IU kg−1 twice‐weekly period, and the 100 IU kg−1 once‐weekly period respectively. Differences in ABR between the first on‐demand period and both prophylaxis regimens were significant (P < 0.0001); no significant differences were observed between prophylaxis regimens (P = 0.22). Seven serious adverse events occurred in five subjects, none related to study drug. Results demonstrated that secondary prophylaxis therapy with nonacog alfa 50 IU kg−1 twice weekly or 100 IU kg−1 once weekly reduced ABR by 89.4% relative to on‐demand treatment. Both prophylaxis regimens demonstrated favourable safety profiles in subjects with haemophilia B.